Prawne i ekonomiczne aspekty relacji gospodarczych Polski i Ukrainy w latach 1991−2008 - Chłopecki, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article exposed the legal basis of the modern economic policy of Kyiv and Warsaw and the impact of EU arrangements for this policy. In the present relations between Poland and Ukraine, Poland is becoming, in some respects, the spokesman of Ukraine in the European Union, trying to connect Ukraine with countries of Central and Western Europe. Ukraine’s political and economic situation and, above all, the possibility and willingness of the Ukrainian authorities to effectively carry out the actual rather than the declared economic reform and thereby reducing the growing disparities in the level of economic development of Poland and Ukraine will have a very big impact on the future development of Polish-Ukrainian relations. It is due to the fact that such politics has consequences for Poland, particularly in the commercial and legal issues. In this issue, the agreement regulating economic relations between the European Union and Ukraine which was concluded in Luxembourg on 14 June 1994 and the Protocol to the Agreement on Partnership and Cooperation between the European Communities and their Member States as one party and Ukraine as the other party concerning a Framework Agreement between the European Union and Ukraine is important. Hence, the role of Poland which seeks to improve the competitiveness of Ukraine within the framework of the investment in the infrastructure of the public sector, improve the business environment and strengthen the public finance sector should be emphasized. These activities are also implemented in the framework of cross-border projects undertaken by local authorities whose task is to increase the activation of their residents by improving the level of public services in the context of a general increase in the effectiveness of reforms in the financial and public sector.
Keywords: Unia Europejska; Polska; Ukraina; prawo; gospodarka